Performance of Hereford Crossbred and Kedah-Kelantan Cattle fed a Palm Kernel Cake-based Ration - Mak, T. K; Hutagalung, R. I.; Togimin, Tokiran; Dass, S (1985)
In a feeding experiment involving the use of a PKC-based ration for·105 days, the average daily feed intake of 3.11 and 3.31 kg in Hereford crossbred and Kedah-Kelantan cattle respectively, was found to be not significant. Hereford crossbred cattle had an average daily gain of O.712 kg which was significantly higher (P < 0.05) than that of Kedah-Kelantan cattle (0.586 kg). Similarly Hereford crossbred cattle had a significantly better (P < 0.01) feed efficiericy (4.37) compared to that of Kedah-Kelantan cattle (5.71). The income overfeed cost per animal per day was $1.344 and $0.514 in Hereford crossbred and Kedah-Kelantan cattle respectively.